2014
DOI: 10.1158/1541-7786.mcr-14-0074
|View full text |Cite
|
Sign up to set email alerts
|

Altered Endosome Biogenesis in Prostate Cancer Has Biomarker Potential

Abstract: Prostate cancer is the second most common form of cancer in males, affecting one in eight men by the time they reach the age of 70. Current diagnostic tests for prostate cancer have significant problems with both false negatives and false positives, necessitating the search for new molecular markers. A recent investigation of endosomal and lysosomal proteins revealed that the critical process of endosomal biogenesis might be altered in prostate cancer. Here, a panel of endosomal markers was evaluated in prosta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 49 publications
5
25
0
Order By: Relevance
“…The previous studies have shown that APPL1 protein promotes invasion and progression of some cancer types by altering early endosome biogenesis [16, 25], provoking alternative TGFβ signaling pathways [15], modulating DNA repair [17], or promoting cell cycle progress [26]. In the present study, we found a novel mechanism of APPL1-directed proliferation and migration of cancer cells by positively regulating leptin signaling pathway.…”
Section: Discussionsupporting
confidence: 62%
“…The previous studies have shown that APPL1 protein promotes invasion and progression of some cancer types by altering early endosome biogenesis [16, 25], provoking alternative TGFβ signaling pathways [15], modulating DNA repair [17], or promoting cell cycle progress [26]. In the present study, we found a novel mechanism of APPL1-directed proliferation and migration of cancer cells by positively regulating leptin signaling pathway.…”
Section: Discussionsupporting
confidence: 62%
“…Expression of appl1 mrna was also higher in gc than in non-gc specimens (p = 0.009). Those results were similar to findings previously reported in prostate cancer 20 and breast cancer 12 .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we focused on changes in APPL1 expression in gastric cancer and the effect of APPL1 on cancer cell metastasis. The results showed that APPL1 protein and mRNA were upregulated both in gastric carcinoma tissue and cultured cell lines, which were consistent with findings previously reported in prostate (8), breast (20) and gastric cancer (19).…”
Section: Discussionsupporting
confidence: 92%
“…Metastasis is the predominant cause of cancer-related mortality in gastric carcinogenesis and the mechanism of tumor metastasis is a multifactorial process associated with multiple genetic and epigenetic events. Previous studies have shown that adaptor proteins promote invasion and migration progression of some cancer types by altering early endosome biogenesis, which could have important implications for cancer cell biomarker release and intracellular signaling (3,7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation